PENGARUH MACAM MEDIA TANAM DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN MUCUNA BRACTEATA - Simanjuntak, Glenn Semeon; Andayani, Neny; Ardiani, Fani (Institut Teknologi Sawit Indonesia, 2023)
The purpose of this study was to determine the effect of planting media and doses of NPK fertilizer on the growth of Mucuna bracteata which had been carried out in the Instiper Yogyakarta educational and research garden (KP-2), located in Wedomertani village, Ngemplak district, Kab. Sleman, Yogyakarta, from February to May 2023. This research was a factorial experiment which was arranged in a Complete Randomized Design (CRD) which consisted of two factors. The first factor was the type of planting medium consisting of 4 levels of pure soil, 1:1 pure soil of cow manure, 1:1 pure soil of goat manure, 1:1 pure soil of rice husk compost. The second factor was the dose of NPK fertilizer which consisted of 4 levels of 0 g, 0.5 g, 0.75 g and 1 g. The research data were analyzed using ANOVA (Analysis of Viriance) and DMRT (Duncan Multiple Range Test) follow-up test of 5%. The results of the analysis showed that the growing medium for cow manure produced the best growth of Mucuna bracteta. The type of planting media on the parameters of the number of leaves, plant fresh weight, plant dry weight, root fresh weight, root dry weight, number of root nodules, number of effective root nodules showed the same growth. The dose of NPK fertilizer showed that all parameters had the same effect on the growth of Mucuna bracteata.